Prevention of Early Marriage and Increasing Awareness of the Importance of Education Through Talk Shows at MA Bahriyatussa’adah: Pencegahan Pernikahan Dini dan Peningkatan Kesadaran Pentingnya Pendidikan Melalui Talk Show di MA Bahriyatussa’adah - Muhammad Ali Zakaria; Akmal Kamil; Sulis Setia Ningsih; Jumra Sagaf; Muhamad Ali Mahdi (Universitas Darunnajah, Jakarta, Indonesia, 2025)
: Education plays a crucial role in improving quality of life and providing better future opportunities. However, the Not in Education, Employment, or Training (NEET) phenomenon and the high rate of early marriage remain significant challenges, particularly in West Java. The Community Service Program (KKN) in Cibodas Village aimed to raise awareness among students of Madrasah Aliyah (MA) Bahriyatussa’adah about the importance of education in preventing early marriage through a talk show titled “Preventing Early Marriage, Creating a Bright Future Through Education”. This activity employed survey-based and interactive counseling methods, featuring expert speakers in marriage law and education. The results indicated an increased awareness among students regarding the importance of higher education and the opportunities available to them after graduation. This program is expected to shift students' and the community's mindset, thereby reducing early marriage rates and increasing participation in higher education.